Victimology: A study of Crime Victims and their Roles (Prentice Hall, 2003)
Giving a voice to the victims in society today this volume was written to raise awareness about the often forgotten victims of crime. Designed to give readers a broader perspective about the experience of victims, this volume provides information on a wide variety of crimes within their individual contexts and demonstrates to readers some of the range of experiences that crime victims are forced to deal with. It addresses victims' support policies and programs and provides a realistic approach to understanding the process of victimization and the broad range of coping mechanisms that victims employ to deal with their particular experience. The volume addresses predators and their targets including serial killers, date rape, professional misconduct, victims of child abuse, female youth gangs, victims of domestic violence and terrorism, hate crime victimization and racial profiling, victims in organizational contexts and responses to victimization. For individuals in criminal justice, psychology and sociology professions with an interest in victims experiences.